CEBPB knockdown sensitizes nasopharyngeal carcinoma cells to cisplatin by promoting the expression of serine protease inhibitor Kazal-type 5. Issue 1 (January 2022) - Liu, Hong; Huang, Qingli; Lv, Yunxia; Dong, Youwei; Song, Daoliang
Abstract : Serine protease inhibitor Kazal-type 5 (SPINK5) has been indicated to act as a prognostic predictor for patients with head and neck squamous cell carcinoma. However, its specific role in nasopharyngeal carcinoma (NPC), a malignancy that has a high propensity for chemoresistance, remains largely obscure. We, thus, sought to investigate the importance of SPINK5 expression in regulating chemoresistance in NPC. Differentially expressed genes in NPC were screened using the cancer genome atlas-head and neck squamous cell carcinoma database and microarray analysis. SPINK5 was downregulated in NPC tissues and cells. After SPINK5 upregulation, the cells treated with cisplatin showed reduced cell survival and the ability to migrate, invade and metastasize. Mechanistically, the transcription factors regulating SPINK5 were queried through the JASPAR website, followed by dual-luciferase and Chromatin immunoprecipitation assay validation. CCAAT enhancer-binding protein (CEBP) beta (CEBPB) bound to the SPINK5 promoter region in NPC cells. The silencing of CEBPB enhanced the expression of SPINK5. CEBPB overexpression reversed the inhibitory effects of cisplatin on NPC cell malignant phenotype in the presence of SPINK5 overexpression. In conclusion, CEBPB silencing promoted chemoresistance of NPC cells via activating SPINK5, signifying that targeting CEBPB was a new approach to enhance the chemotherapy efficacy in NPC.